Local endoreduplication of the host is a conserved process during Phytomyxea–host interaction - Hittorf, Michaela; Garvetto, Andrea; Magauer, Marianne; Kirchmair, Martin; Salvenmoser, Willibald; Murúa, Pedro; Neuhauser, Sigrid (Frontiers in Microbiology, 2025)
BackgroundEndoreduplication, a modified cell cycle, involves cells duplicating DNA without undergoing mitosis. This phenomenon is frequently observed in plants, algae, and animals. Biotrophic pathogens have been demonstrated to induce endoreduplication in plants to secure more space or nutrients.MethodsIn this study, we investigated the endoreduplication process triggered by two phylogenetically distant Rhizaria organisms—Maullinia spp. (in brown algae) and Plasmodiophora brassicae (in plants)—by combining fluorescent in situ hybridization (FISH) with nuclear area measurements.ResultsWe could confirm that Plasmodiophora brassicae (Plasmodiophorida) triggers endoreduplication in infected plants. For the first time, we also demonstrated pathogen-induced endoreduplication in brown algae infected with Maullinia ectocarpii and Maullinia braseltonii (Phagomyxida). We identified molecular signatures of endoreduplication in RNA-seq datasets of P. brassicae-infected Brassica oleracea and M. ectocarpii-infected Ectocarpus siliculosus.DiscussionCell cycle switch proteins such as CCS52A1 and B in plants, CCS52 in algae, and the protein kinase WEE1 in plants were upregulated in RNA-seq datasets hinting at a potential role in the phytomyxean-induced transition from mitotic cell cycle to endocycle. By demonstrating the consistent induction of endoreduplication in hosts during phytomyxid infections, our study expands our understanding of Phytomyxea–host interaction. The induction of this cellular mechanism by phytomyxid parasites in phylogenetically distant hosts further emphasizes the importance of endoreduplication in these biotrophic interactions.